2013
DOI: 10.5812/hepatmon.13787
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid: From Biochemical Characteristics to its Clinical Translation in Assessment of Liver Fibrosis

Abstract: Context:Hyaluronic acid (HA) is a high molecular weight polysaccharide that is distributed in all bodily tissues and fluids. The liver is the most important organ involved in the synthesis and degradation of HA. Research has shown that liver cell injury can affect serum HA levels. In this review, authors aimed to describe the biochemical and physiological roles of this glycosaminoglycan and its changes in various liver diseases.Evidence Acquisition:Liver fibrosis and in more severe form, cirrhosis are results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 46 publications
1
57
1
4
Order By: Relevance
“…Some researchers report that HA is an accurate noninvasive marker in predicting significant F in HD patients with hepatitis C [1,37,38], but we found no studies on the utility of HA in predicting F in chronic VHB. Chen et al [39] showed that HA, laminin (LN), procollagen III N-terminal peptide (PIIINP), and type IV collagen (CIV) were correlated with F in chronic VHB.…”
Section: Discussioncontrasting
confidence: 49%
“…Some researchers report that HA is an accurate noninvasive marker in predicting significant F in HD patients with hepatitis C [1,37,38], but we found no studies on the utility of HA in predicting F in chronic VHB. Chen et al [39] showed that HA, laminin (LN), procollagen III N-terminal peptide (PIIINP), and type IV collagen (CIV) were correlated with F in chronic VHB.…”
Section: Discussioncontrasting
confidence: 49%
“…The accumulation of HA can result as a consequence of activated hepatic stellate cell production or reduced hepatic sinusoidal endothelial cell clearance [28]. Several studies supports that HA level and FIB-4 score may be clinically useful as a non-invasive marker for liver fibrosis and/or cirrhosis [29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitations of liver biopsy, non-invasive serum biomarkers have been proposed to assess liver fibrosis stage. Hyaluronic acid (HA) is recognized as one the oldest such serum biomarkers (14). First characterized by Meyer and Palmer (15), HA is a high molecular weight linear polymer made up of repeating N-acetyl-glucosamine and β-glucuronic acid disaccharide units, with an abundant distribution throughout numerous species (16).…”
Section: Introductionmentioning
confidence: 99%